The Price Incentive to Smuggle and the Cocoa Supply in Ghana, 1950-96 - Bulir, Ales (IMF Working Papers; Working Paper, 1998)
From the early 1960s to the early 1980s, the officially recorded production of cocoa in Ghana declined by 60 percent. During the 1983-95 Economic Recovery Program, however, cocoa production doubled. Although these developments have inspired much empirical research, most of the studies have been unable to explain the medium-term persistence of cocoa output to remain below its estimated capacity level. The paper argues that the price incentive to smuggle can explain as much as one-half of the observed decline in output and the subsequent recovery. A cointegration analysis and a dynamic error-correction model of cocoa supply support the analysis.